Selenium Alleviates Low-Temperature Stress in Rice by Regulating Metabolic Networks and Functional Genes - Naixin Liu; Qingtao Yu; Baicui Chen; Chengxin Li; Fanshan Bu; Jingrui Li; Xianlong Peng; Yuncai Lu (Agriculture, 2025)
Low temperature is a major abiotic stress affecting rice productivity. Selenium (Se) treatment has been shown to enhance plant resilience to cold stress. In this study, low concentrations of selenium (ColdSe1) alleviated the adverse effects of cold stress on rice seedlings, improving fresh weight, plant height, and chlorophyll content by 36.9%, 24.3%, and 8.4%, respectively, while reducing malondialdehyde (MDA) content by 29.1%. Se treatment also increased the activities of antioxidant enzymes, including catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD), by 25.2%, 42.7%, and 33.3%, respectively, and upregulated flavonoids, soluble sugars, cysteine (Cys), glutathione (GSH), and oxidized glutathione (GSSG). Transcriptome analysis revealed that ColdSe1 treatment upregulated genes associated with amino and nucleotide sugar metabolism, glutathione metabolism, and fructose and mannose metabolism. It also alleviated cold stress by modulating the MAPK signaling pathway, phytohormone signaling, and photosynthesis-related pathways, enriching genes and transcription factors linked to antioxidant metabolism and photosynthesis. Metabolomic analyses showed that ColdSe1 positively influenced amino acid glucose metabolism, glycerolipid metabolism, hormonal pathways, and alanine/glutamate pathways under cold stress, while also upregulating metabolites associated with plant secondary metabolites (e.g., flavonoids, phenolic compounds) and antioxidant metabolism (e.g., α-linolenic acid metabolism). In contrast, high selenium concentrations (ColdSe2) disrupted phenylpropanoid biosynthesis, α-linolenic acid metabolism, and ABC transporter function, exacerbating cold-stress injury. This study highlights the critical role of Se in mitigating cold stress in rice, offering a theoretical basis for its application as an agricultural stress reliever.